2018
DOI: 10.1002/jez.2198
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural land use creates evolutionary traps for nesting turtles and is exacerbated by mercury pollution

Abstract: The rate of anthropogenic habitat conversion often exceeds the rate of natural ecological and evolutionary processes, which sometimes creates mismatches between environmental cues and adaptive behaviors. In numerous species of aquatic turtles, nest site selection is primarily based on cues related to high solar exposure, which leads females to select sites where humans have disturbed habitat. These disturbed sites are often contaminated by pollutants, such as mercury. Despite the fact that anthropogenic distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 98 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…At the landscape level (7680 m), the relationship between sex ratio and crop cover appears to follow the opposite trend, with proportion of males captured increasing with greater crop cover. This pattern may reflect the potential cooling effect that mature crops can have on nests (Mui et al, 2016; Thompson, Coe, Andrews, Cristol, et al, 2018). Given that females typically nest near wetlands (Beaudry et al, 2010) and rarely, if ever, travel more than a few hundred meters to nest (Steen et al, 2012), this relationship may reflect a component of spotted turtle ecology that operates at a larger spatial scale, such as male dispersal distance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the landscape level (7680 m), the relationship between sex ratio and crop cover appears to follow the opposite trend, with proportion of males captured increasing with greater crop cover. This pattern may reflect the potential cooling effect that mature crops can have on nests (Mui et al, 2016; Thompson, Coe, Andrews, Cristol, et al, 2018). Given that females typically nest near wetlands (Beaudry et al, 2010) and rarely, if ever, travel more than a few hundred meters to nest (Steen et al, 2012), this relationship may reflect a component of spotted turtle ecology that operates at a larger spatial scale, such as male dispersal distance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the urban heat island effect has the potential to generate female‐biased populations in urbanized settings via TSD (for species that produce females at higher temperatures; discussed by Bowne et al, 2018). Conversely, row crops can act as ecological traps by presenting suitable incubation conditions during the nesting period, but producing considerably cooler temperatures once crop growth progresses, ultimately leading to male‐skewed clutches (Freedberg et al, 2011; Thompson, Coe, Andrews, Cristol, et al, 2018; Thompson, Coe, Andrews, Stauffer, et al, 2018). Freshwater turtles are also widely considered susceptible to differential mortality among sexes driven by land use, whereby male‐biased sex ratios are produced due to increased vulnerability of females during nesting forays (Aresco, 2005; Steen et al, 2006; Steen & Gibbs, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This section contains four original research papers that examine the potential consequences of warming temperatures and pollutants on development of reptile embryos. First, Thompson et al (2018) demonstrated that snapping turtle embryos are negatively affected by shaded conditions in agricultural fields, as well as by mercury pollution at these sites. Sanger, Kyrkos, Lachance, Czesney, and Stroud (2018) demonstrated that increasing temperatures negatively affect embryo survival during the stages of morphogenesis in brown anoles, and suggest that climate change will likely negatively affect egg survival given that nests in the field are currently at the thermal limits.…”
Section: Global Change Biology and Conservationmentioning
confidence: 99%
“…Plasticity of the embryonic cardiovascular system in crocodilians has been the focus of several recent investigations. The American alligator (Alligator mississippiensis; Duadin, 1801) undergoes both morphological and physiological changes in response to fluctuations in O 2 availability during development (8,9,(11)(12)(13)(14)(15)(16). Specifically, egg incubation in 10% O 2 induces changes in protein composition of cardiac tissue, cardiac growth, blood pressure, and cardiovascular regulatory mechanisms of embryonic alligators (14,15,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%